The phenomenon of the intermediary in the context of the cultural challenges of the forwarding process on the example of the company Landi Sp. z o.o. - Fudali, Jan (Contemporary challenges of transport, freight forwarding and logistics - selected aspects, 2023)
The purpose of the study of this chapter is to analyze the problems of the forwarding process on the example of the company Landi Sp. z o.o. The authors, on the basis of conducted 40 free interviews forwarders and dispatchers, in enterprises Landi Sp. z o.o. described the specifics of the forwarding process through the prism of cultural differences affecting the course of the transport process at all its stages. A major challenge here is the phenomenon referred to as the 'intermediary phenomenon' whereby cooperating actors are joined by another who comes from a different culture. The conclusions indicate that from the point of view of the Polish carrier (subcontractor), as well as the Western customer, and the Eastern driver, the process is a mosaic of difficulties, where without adequate preparation in terms of intercultural competence, it is very difficult to avoid mistakes, misunderstandings, or keep emotions in check.